PENGARUH KONTEN CHANNEL YOUTUBE GADGET IN TERHADAP KEBUTUHAN INFORMASI SUBSCRIBER - Rayhan Ibrahim; Muhammad Darwinsyah (Jurnal Sarjana Ilmu Komunikasi (J-SIKOM), 2026)
The transformation of media driven by the development of digital technology has changed the way people obtain information. YouTube, as a new medium, serves not only as a platform for entertainment but also as a primary source for meeting the public’s information needs, including on technology-related topics. This study aims to determine the influence of the GadgetIn YouTube channel’s content on the information needs of its subscribers. Using a quantitative approach, this study involved 100 active respondents from a total population of 13.4 million subscribers to the GadgetIn YouTube channel. Sampling was conducted using a non-probability method based on the Slovin formula. Data collection was conducted through the distribution of an online questionnaire designed based on YouTube channel content indicators according to Jacky Maulana (2021) and information needs according to Syaffril (in Perdana et al., 2012:5). The results of the validity and reliability tests showed that all instruments had valid and consistent values. Through simple linear regression analysis, the results showed that GadgetIn content has a positive influence on information needs, with a coefficient of determination of 70.9%. It was found that the type of information, visual appeal, frequency, and viewing duration collectively influence the search for knowledge related to the development of digital devices. This study concludes that GadgetIn’s content contributes to enhancing viewers’ technological knowledge. Therefore, the optimization of relevant and targeted content delivery needs to be continuously developed to address the specific needs of subscribers in navigating the flow of digital information. The results of this study are expected to serve as an academic and practical reference in the development of technology-based content media strategies. Keywords: YouTube, Gadget Content, Information Needs, Customers, GadgetIn